Developing a Learning Style-Oriented Small Private Online Course (SPOC) with Norm- Referenced Testing (NRT) Integration - Ibnu Nur Akhsan; Basuki Wibawaa; Robinson Situmoranga (International Journal of Computational and Experimental Science and Engineering, 2025)
This research explores the development of Small Private Online Courses (SPOC) to address the limitations of MOOCs, particularly in personalization and learning effectiveness. A survey of 140 students revealed that 92.9% preferred materials suited to their learning styles (visual, auditory, kinesthetic), 63.8% sought integration with automotive-related mathematics, and 73% desired flexible yet private online learning. Using the Borg & Gall R&D model for needs analysis and the Dick & Carey approach for development, this study designed a learning style- based SPOC. Expert validation confirmed its feasibility, and statistical analysis (Pearson correlation, Cronbach's Alpha) ensured its reliability. The effectiveness evaluation showed moderate learning gains (N-Gain: 0.64-0.66) and significant improvements based on a Paired Sample T-test. Observations indicated enhanced engagement, attitudes, and interest. Implementing SPOC with learning style-based grouping fosters collaborative, immersive learning, improving effectiveness in vocational education.